Efeitos da presença de adversário no desempenho físico de atletas competitivos e não atletas em contrarrelógio de 30-km de ciclismo - Thiago Teixeira Mendes (2017)
Opponent presence manipulation seems to improve physical performance during high-intensity and short-term exercise in physically active individuals, athletes and non-athletes. However, the effect of opponent's presence on performance during prolonged physical exercise is not clear. Thus, the aim of the present study was to evaluate the effects of the virtual opponents presence on a 30-km cycling time-trial performance in both competitive cyclists and non-athlete subjects. Twenty-four healthy men (12 competitive cyclists CC group and 12 non-athlete subjects NCC group) aged between 18 and 36 years were subjected to five experimental situations in which a 30-km cycling time-trial performance was carried out on a bike with gears, coupled to an electromagnetic brake system. After familiarization, a control test was undertaken to determine physical performance to be further used in order to manipulate the virtual opponents performance. Subsequently, two experimental situations were randomly performed: either with or without virtual opponent simulation (COMP102% - with competition and SELF - time-trial condition without competition respectively). The virtual opponent performance was set 2% higher than the previous performance of each subject. Physiological and perceptive/psychological data were recorded at every 5.0 km. CC group showed higher motivational profile to compete when compared to NCC group. However, no difference was found in physical performance improvements between the two groups due to virtual opponent presence. In addition, there was no significant correlation between changes in physical performance owing to virtual opponent presence and the subjects motivational profile. In contrast, CC group showed higher motivation score in every trial situations. Nevertheless, no motivation changes were observed in the CC group under opponents presence, whereas the NCC group showed higher motivation. In conclusion, opponent presence influenced the fatigue and increased, in a similar way, physical performance of both CC and NCC, despite differences in motivation profiles for competition during a 30-km cycling time-trial.